Removal of Arsenic and Chromium Oxyanions by Hydrous Tin Dioxide and Tin(IV)-Loaded Exchangers - Tan, Wee Chang (2005)
The potential of tin-loaded poly(hydroxamic acid) ion exchange resin (SnPHA), hydrous tin dioxide (SnO2.xH2O) and hydrous tin dioxide-loaded poly(hydroxamic acid) resin (SnOPHA) to remove heavy metals As(V), As(III) and Cr(VI) from aqueous solution was investigated. Poly(hydroxamic acid) resin was prepared from poly methyl acrylate-divinyl benzene copolymer (PMA). The ester group of the PMA was converted to the hydroxamic acid using the hydroxylamine in an alkaline solution. The SnPHA was prepared by shaking the PHA resin with SnCl4 solution. SnO2.xH2O was prepared by neutralizing a Sn(IV) chloride solution with ammonia solution. The XRD result proved that the SnO2.xH2O prepared is pure. The SnOPHA was produced by direct treating SnPHA with ammonia solution. The XRD result also contributed clear information about the oxidation stated of Sn(IV) in the PHA resin.